Día de Muertos v současném Mexiku: Proměna mexické tradice - Ponocná, Petra (Lidé města, 2015)
Día de Muertos, the Mexican celebration of death, is considered to be a traditional Mexican celebration by most Mexicans. The majority of them believe that the specificity and magnificence of this feast are unprecedented. Día de Muertos is a product of the syncretism of the Mesoamerican traditions of worshipping the dead and the Catholic celebrations of All Saints’ and All Souls’ Day. Besides this, it is considered to be traditional commemorative ritual; it is also considered to be a symbol of Mexican national identity, and the celebration is supported by Mexican nationalists. Over the past 30 years, the celebration has evolved dramatically and has been influenced by American holiday of Halloween, which is celebrated by more and more people thanks to the influence of modernisation. Despite the fact that the Día de Muertos celebration may seem to be uniform, its local versions differ slightly. The aim of this paper is to describe and to analyse the process of the contemporary changes in this celebration and to approximate its importance in Mexican society, particularly in Querétaro city and in the Xochimilco district in Mexico City. For my research, I used the ethnographic methods of participant observation and interviews.